A Theory of Strategic Diffusion - Sanjeev Goyal; Andrea Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2007)
The important role of friends, neighbors and colleagues in shaping individual choices has been brought out in a number of studies over the years. The presence of significant local influence in shaping individual behavior suggests that firms, governments and developmental agencies should explicitly incorporate it in the design of their marketing and developmental strategies. This paper develops a framework for the study of optimal strategies in the presence of social interaction. We focus on the case of a single player who exerts costly effort to get a set of individuals engaged in social interaction to choose a certain action. Our formulation allows for different types of social interaction (ranging from sharing of information to direct adoption externalities) and also allows for the player to have incomplete information concerning the connections among individuals. The analysis starts by showing that incorporating information on social interaction can have large effects on the profits of a player. We then show that an increase in the level and dispersion of social interaction can raise or lower the optimal strategy and profits of the player, depending on the content of the interaction. We then study the value of social network information for the player and find that it depends on the dispersion in social connections. The economic interest of these results is illustrated via a discussion of two economic applications: advertising in the presence of word of mouth communication and seeding a network.
Keywords: D8; L15; 330; Social Interaction; Seeding the Network; Word of Mouth Communication; Diffusion Strategy; Soziale Beziehungen; Werbung; Kommunikation; Theorie